Illuminiertes Bornhöved – eine außergewöhnliche Hügelkonstruktion der Bronzezeit - Kneisel, Jutta (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
North of Bornhöved, district of Segeberg, remains of an unusual burial mound with a ditch and a post henge were found in summer 2018 in a new development area. The barrow belongs to a group of 5 mounds dating to the Older Bronze Age. In cooperation with the Archäologisches Landesamt Schleswig-Holstein and the municipality of Bornhöved, the tumulus was investigated over a large area in 2018 by the project D 3 within the CRC 1266, University of Kiel. The tumulus stands out due to its unusual construction. The central grave was surrounded by a repeatedly excavated ditch, stone circle, stone packing and post henge. Extensive botanical and geological investigations point to a mound that was repeatedly reshaped, enlarged and modified with new features. The highlight of the site was certainly a fire that enclosed the mound in a circle of flames. The burial mound was also later used as a burial place. Seven urn graves partly preserved under a colluvium (Younger Bronze Age) and three stratigraphically younger oval stone pavements bear witness to this. Settlement traces were found in the south-west of the mound with a waste pit below a cultural layer and postholes dating to the Bronze or Iron Age. The article will highlight the complex phases of use of the barrow over the centuries from the Late Neolithic to the Bronze Age and beyond. This type of complex burial construction is typical of the Late Neolithic / Older Bronze Age, but rarely attested in Schleswig-Holstein and Denmark. Rather, the unusual construction points to parallels in the West, the Netherlands and Belgium.